Chemical thermal storage medium composition, and production method and use of the same

The chemical heat storage material composition with MgCl2 and NH3, utilizing a thermal addition crosslinking silicone elastomer, addresses volume changes and increases heat output rate, enabling efficient thermal energy storage and recovery.

JP2025007161APending Publication Date: 2025-01-17INSTITUTE OF SCIENCE TOKYO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108373
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Chemical heat storage materials using MgCl2 and NH3 experience volume changes during heat absorption and generation, leading to decreased heat storage/heat output density and rate, and low absorption reactivity at around 100°C, hindering practical use.

Method used

A chemical heat storage material composition comprising metal chloride (MCl2) and ammonia (NH3) with a predetermined shape, using a thermal addition crosslinking type silicone elastomer to suppress volume changes and increase heat output rate, achieved through pressure molding and activation pretreatment.

Benefits of technology

The composition effectively suppresses volume changes and enhances heat output rate in the low temperature range of around 100°C, ensuring practical usability and efficient thermal energy storage and recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007161000001_ABST
    Figure 2025007161000001_ABST
Patent Text Reader

Abstract

To suppress volume change when operating in a MCl2 / NH3-based chemical thermal storage medium which can be used in a low temperature region, and provide an activation method for heightening a thermal output rate of such chemical thermal storage medium.SOLUTION: A chemical thermal storage medium composition having a predetermined shape includes a chemical thermal storage medium composed of a metal chloride (MCl2), and ammonium (NH3); and an elastomer. An activation method includes: reacting anhydrous MgCl2 with NH3 at a first temperature to generate MgCl2 6 NH3; and thereafter eliminating NH3 by heating MgCl2 6 NH3 at a second temperature higher than the first temperature under an environment of NH3 to generate MgCl2 2 NH3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemical thermal storage material composition having improved durability, as well as a method for producing and using such a chemical thermal storage material composition. [Background technology]

[0002] With the rise in environmental awareness, research and development is actively being conducted to save energy and improve energy efficiency. One of these is a chemical heat storage system that uses a chemical heat storage material that has a high heat storage density and can store heat for a long period of time without heat retention. This makes it possible to effectively utilize relatively low-temperature waste heat (exhaust heat) generated by various devices and plants.

[0003] Chemical heat storage technology includes a technology for immobilizing ammonia (NH3) in metal chloride (MCl2), and it is known that, for example, chlorides of alkaline earth metals and transition metals generate or absorb heat when absorbing or desorbing ammonia. Recently, metal chlorides that form ammonia complexes that can operate in lower temperature ranges have been used, and for example, a chemical heat storage device using MgCl2 as the metal chloride has been disclosed (Patent Document 1).

[0004] When MgCl2 reacts with NH3, it gradually changes into the compounds MgCl2·NH3, MgCl2·2NH3, and MgCl2·6NH3. The equilibrium temperature of each reaction changes depending on the NH3 pressure during the reaction, and in particular the reaction MgCl2·2NH3+4NH3⇔MgCl2·6NH3 proceeds at around 100°C. The progression of a chemical reaction means the conversion of thermal energy to chemical (bond) energy, and the above reaction suggests its applicability as a chemical heat storage material in such low temperature ranges. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-14234 A [Patent Document 2] JP 2016-190990 A Summary of the Invention [Problem to be solved by the invention]

[0006] It is known that the above-mentioned equilibrium reaction between MgCl2 and NH3 is accompanied by a volume change of the chemical heat storage material. In practical use of the chemical heat storage material, the occurrence of a volume change during the absorption / exothermal generation is undesirable because it reduces the heat storage / heat output density and heat storage / heat output rate per unit volume. In general, chemical heat storage materials are used by mixing with a binder to form them into pellets in order to increase the thermal conductivity compared to powder and to make them easier to handle. However, conventional pelletizing methods are insufficient to suppress the volume change associated with the equilibrium reaction between MgCl2 and NH3 and prevent the collapse of the pellets.

[0007] As mentioned above, the MgCl2 / NH3 system as a chemical heat storage material has an equilibrium temperature at which the reaction proceeds around 100°C, suggesting its potential for use in low temperature ranges. However, the reactivity of NH3 absorption at around 100°C is low, and the heat output rate required for practical use as a chemical heat storage material has not yet been achieved.

[0008] The present invention has been made in view of the above problems, and aims to suppress the volume change during operation to a practical level in the MCl2 / NH3 system, which is expected to be usable as a chemical heat storage material in the low temperature range, in particular. In addition, it also aims to provide an activation method for increasing the heat output rate in the low temperature range of around 100°C. [Means for solving the problem]

[0009] According to the present invention, there is provided a chemical heat storage material composition having a predetermined shape, comprising a chemical heat storage material made of a metal chloride (MCl2) and ammonia (NH3), and an elastomer. In the chemical thermal storage medium composition according to the present invention, the elastomer is preferably a thermal addition crosslinking silicone elastomer. In addition, in the chemical heat storage material composition according to the present invention, the metal M of the metal chloride (MCl2) is preferably selected from the group consisting of magnesium (Mg), nickel (Ni), calcium (Ca), lead (Pb), cobalt (Co), copper (Cu), zinc (Zn) and manganese (Mn). In addition, in the chemical heat storage material composition according to the present invention, the metal chloride is preferably MgCl2. In addition, in the chemical thermal storage medium composition according to the present invention, the mass ratio of the elastomer to the metal chloride is preferably within the range of 0.1 to 0.7.

[0010] Further, according to the present invention, there is provided a method for producing a chemical thermal storage medium composition having a predetermined shape, which comprises: preparing a precursor composition by mixing a metal chloride (MCl2) and an elastomer precursor in a predetermined ratio; pressurizing the precursor composition to prepare a precursor composition having a predetermined shape; polymerizing the elastomer precursor by heating the precursor composition having the predetermined shape; and subjecting the composition having the predetermined shape after the polymerization to an activation pretreatment in which ammonia (NH3) is absorbed. In the method for producing a chemical thermal storage medium composition according to the present invention, the elastomer precursor is preferably a thermal addition crosslinkable silicone. In addition, in the manufacturing method of the chemical heat storage material composition according to the present invention, the metal M of the metal chloride (MCl2) is preferably selected from the group consisting of magnesium (Mg), nickel (Ni), calcium (Ca), lead (Pb), cobalt (Co), copper (Cu), zinc (Zn) and manganese (Mn). In addition, in the method for producing a chemical thermal storage medium composition according to the present invention, the mass ratio of the elastomer precursor to the metal chloride is preferably within the range of 0.1 to 0.7.

[0011] Furthermore, according to the present invention, there is provided a method for activating a chemical heat storage material consisting of magnesium chloride (MgCl2) and ammonia (NH3), characterized in that the raw material anhydrous MgCl2 is reacted with NH3 at a first temperature to generate MgCl2·6NH3, and then the MgCl2·6NH3 is heated in an NH3 atmosphere to a second temperature higher than the first temperature to desorb NH3 and generate MgCl2·2NH3. In the activation method according to the present invention, it is preferable that the first temperature is room temperature and the second temperature is 200° C. or lower.

[0012] Furthermore, according to the present invention, there is provided use of the above-mentioned chemical heat storage material composition as a chemical heat pump combining an NH3 absorption exothermic reaction and an NH3 desorption endothermic reaction. Effect of the Invention

[0013] The chemical heat storage material composition according to the present invention can suppress the volume change during operation to a practical level in the MCl2 / NH3 system as a chemical heat storage material operating in a low temperature range of around 100° C. Furthermore, the chemical heat storage material composition according to the present invention can increase the heat output rate in the above low temperature range in the MCl2 / NH3 system. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a process diagram showing a procedure for preparing composite pellets using MgCl2 and silicone rubber. [Diagram 2] 1 is a graph showing the NH3 absorption behavior in the first cycle in a repeated reaction test at 120° C. using a composite pellet-shaped chemical thermal storage material. [Diagram 3] 1 is a graph showing the NH3 absorption behavior in the 10th cycle in a repeated reaction test at 120° C. using a composite pellet-shaped chemical thermal storage material. [Figure 4] 4 is a photograph showing the appearance of a composite pellet before and after a repeated reaction test. [Diagram 5]1 is a graph showing the heat storage density and heat storage rate per unit volume of a chemical heat storage material. [Figure 6] 1 is a graph showing the thermal output density and thermal output rate per unit volume of a chemical thermal storage material. [Figure 7] 1 is a graph showing the results of an operation demonstration test using a composite pellet-shaped chemical heat storage material as a chemical heat pump. [Figure 8] This is a process diagram showing the sample preparation procedure and reaction conditions for MgCl2 / NH3-based chemical thermal storage material with and without activation pretreatment. [Figure 9] 1 is a graph showing the change over time in (a) the amount of NH3 absorbed and (b) the absorption rate in a MgCl2 / NH3-based chemical thermal storage material with or without activation pretreatment. [Figure 10] 1 is a graph showing (a) the amount of NH3 absorbed over all cycles and (b) the change over time in the amount of NH3 absorbed during the absorption process in each cycle in a repeated reaction test at 100°C of a MgCl2 / NH3-based chemical heat storage material that has been subjected to activation pretreatment. [Figure 11] This is a graph showing (a) the amount of NH3 absorption and the change in temperature over time for the entire cycle, and (b) the amount of NH3 absorption and desorption change for each cycle, as a result of an operation demonstration test using a MgCl2 / NH3-based chemical heat storage material that had been subjected to activation pretreatment as a chemical heat pump. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The chemical heat storage material composition according to the present invention comprises a chemical heat storage material consisting of a metal chloride (MCl2) and ammonia (NH3), and an elastomer, and has a predetermined shape. The metal M constituting the metal chloride (MCl2) may be any metal capable of causing a reversible gas-solid reaction with ammonia (NH3) and storing thermal energy as chemical energy. Specific examples of such metal M include magnesium (Mg), nickel (Ni), calcium (Ca), lead (Pb), cobalt (Co), copper (Cu), zinc (Zn), and manganese (Mn).

[0016] For example, when the metal M is Mg, MgCl2 (solid) reacts with NH3 (gas) and gradually changes into the compounds MgCl2·NH3 (solid), MgCl2·2NH3 (solid), and MgCl2·6NH3 (solid). The equilibrium temperature of each reaction changes depending on the NH3 pressure during the reaction, and in particular, the reaction MgCl2·2NH3+4NH3⇔MgCl2·6NH3 proceeds at around 100°C. Here, the absorption reaction of NH3 (MgCl2·2NH3+4NH3→ MgCl2·6NH3) is an exothermic reaction, which is the heat output process of the chemical heat pump. Conversely, the desorption reaction of NH3 (MgCl2·6NH3→ MgCl2·2NH3+4NH3) is an endothermic reaction, which is the heat storage process of the chemical heat pump. In addition, since the boiling point of NH3 is -33°C, this chemical heat pump can be started in a cold atmosphere.

[0017] The elastomer contained in the chemical heat storage material composition according to the present invention may be any elastomer capable of substantially maintaining the predetermined shape given to the chemical heat storage material composition. In general, the volume of the solid of the chemical heat storage material changes during the above-mentioned reversible gas-solid reaction. For example, MgCl2·6NH3, which is generated when MgCl2 absorbs NH3, has an apparent volume that is about four times that of MgCl2. Such volume expansion of the material is undesirable because it leads to a decrease in the heat storage density or heat output density per unit volume of the chemical heat storage material. In addition, chemical heat storage materials are generally formed into a predetermined shape such as pellets in order to increase thermal conductivity compared to powder and to make them easier to handle. Therefore, it is necessary to suppress the volume change associated with the equilibrium reaction between MgCl2 and NH3 and prevent the collapse of the predetermined shape.

[0018] The elastomer according to the present invention must be selected taking into consideration the conditions specific to the reaction system of the MCl2 / NH3-based chemical heat storage material. For example, considerations include chemical resistance to the heat transfer medium NH3, heat resistance in the operating temperature range of the chemical heat storage material, and the ability to ensure the diffusibility of NH3 gas to MCl2 contained in the elastomer when composited with MCl2. In addition, when using a low-cost material such as MgCl2 as the chemical heat storage material, the cost of the elastomer itself may also be a consideration.

[0019] A technology is known that uses silicone polymer as a binder material to prevent the collapse of a chemical heat storage material. For example, Patent Document 2 (JP Patent Publication 2016-190990A) discloses that a dealcoholization condensation type silicone in which a dense three-dimensional structure is formed by condensation of alkoxysilane or the like is combined with a chemical heat storage material. However, since dealcoholization condensation type silicone requires moisture in the air during condensation (curing), in a chemical heat storage material that absorbs moisture and deliquesces, such as MgCl2, magnesium oxide (MgO), which does not react with NH3, is generated during the combination, and the function as a chemical heat storage material may be impaired.

[0020] In addition to the above-mentioned condensation type, silicone polymerization methods include a thermal addition type that requires heat treatment. The thermal addition type has the advantage that it can be cured in a short time by heating and does not generate harmful by-product gases during curing. Therefore, it is preferable that the elastomer used as the binder material in the reaction system of the MCl2 / NH3-based chemical thermal storage material is a thermal addition crosslinking type silicone elastomer. The thermal addition crosslinking type silicone elastomer is obtained by crosslinking and curing by the addition reaction (hydrosilylation reaction) between a vinyl group bonded to silicon contained in the elastomer precursor and a hydrogen group bonded to another silicon, as shown in the following formula. [ka] This hydrosilylation reaction proceeds in the presence of a platinum catalyst, for example, by heating at 120°C for 1 hour. In addition, the hydrosilylation reaction does not require moisture in the air, and does not produce by-products like dealcohol condensation type silicone, so the function of the chemical heat storage material such as MgCl2 is not impaired during the composite formation.

[0021] In the chemical heat storage material composition according to the present invention, the mass ratio of the elastomer to the metal chloride (MCl2) is preferably within the range of 0.1 to 0.7. If the mass ratio of the elastomer is less than 0.1, the chemical heat storage material composition is prone to collapse. If the mass ratio of the elastomer exceeds 0.7, the heat storage density per unit volume of the chemical heat storage material composition decreases. The lower limit of the mass ratio of the elastomer to MCl2 is preferably 0.2 or more, and more preferably 0.25 or more. The upper limit of the mass ratio is preferably 0.6 or less, and more preferably 0.5 or less.

[0022] The chemical thermal storage material composition having a predetermined shape according to the present invention is produced by mixing a metal chloride (MCl2) and an elastomer precursor in a predetermined ratio to prepare a precursor composition, pressurizing the precursor composition to prepare a precursor composition having a predetermined shape, heating the precursor composition having the predetermined shape to polymerize the elastomer precursor, and performing an activation pretreatment to absorb ammonia (NH3) into the composition having the predetermined shape after polymerization. The metal M constituting MCl2 is as described above.

[0023] The elastomer precursor may be any one that can substantially maintain the predetermined shape given to the precursor composition by pressure molding after heat polymerization. For example, one-liquid room temperature vulcanization silicone rubber (Room Temperature Vulcanization or RTV rubber) manufactured by Shin-Etsu Chemical Co., Ltd. is useful as a precursor of the above-mentioned preferred thermal addition crosslinking type silicone elastomer. RTV rubber is a liquid or paste-like product in which reactive polysiloxane (main component), silane compound (crosslinking agent) having a reactive functional group (vinyl group), and polymerization catalyst are integrated. RTV rubber has advantages such as being able to be cured in a short time by heating, being easy to cure deep inside the shaped body, and not generating by-products during curing. Note that since the RTV rubber before curing is a one-liquid type, it needs to be stored in a refrigerator at 10°C or less. The mixing ratio of MCl2 to the elastomer precursor corresponds to the mass ratio of the elastomer to MCl2 described above, and is preferably within the range of 0.1 to 0.7.

[0024] When mixing MCl2 and RTV rubber, MCl2 and RTV rubber may be mixed in an arbitrary mass ratio under an inert atmosphere such as argon (Ar). The obtained precursor composition is then placed in a die for tablet molding and pressure molded to prepare a precursor composition having a predetermined shape such as pellets. There is no particular restriction on the conditions for pressure molding, and normal tablet molding conditions may be applied while paying attention not to cause substantial polymerization of the elastomer precursor. Next, the precursor composition having a predetermined shape obtained by pressure molding is heated to a temperature at which the elastomer precursor polymerizes. When RTV rubber is used as the elastomer precursor, a heating temperature of about 130°C and a heating time of about 2 hours are sufficient. By polymerizing the elastomer precursor while maintaining the predetermined shape such as a pellet shape, a strong crosslinked structure due to siloxane bonds is formed inside the pellet. In this respect, it is different from the structure resulting from simple bonding between elastomer particles formed inside a pellet that is pressure molded by mixing the polymerized elastomer.

[0025] After polymerizing the elastomer precursor, the composition having a predetermined shape is subjected to an activation pretreatment in which ammonia (NH3) is absorbed. As described above, the MgCl2 / NH3-based chemical heat storage material has an equilibrium temperature at which the reaction proceeds near 100°C, but since the reactivity of NH3 absorption near 100°C is low, a sufficient heat output rate has not been obtained for practical use as a chemical heat storage material in the low temperature range. The inventors have intensively studied an activation method for increasing the heat output rate in such a low temperature range, and have found that the heat output rate in the low temperature range of around 100°C can be increased by first reacting the raw material anhydrous MgCl2 with NH3 at a first temperature to generate MgCl2·6NH3, and then heating MgCl2·6NH3 to a second temperature higher than the first temperature in an NH3 atmosphere to desorb NH3 and generate MgCl2·2NH3. Without being bound by any particular theory, it is believed that such activation pretreatment forms a diffusion path for NH3 gas in the anhydrous MgCl2, thereby improving the absorption and desorption reactivity of NH3 in MgCl2·2NH3. Here, the first temperature may be room temperature, and the second temperature is higher than room temperature and not higher than 200°C, preferably not higher than 170°C. An example of a process diagram showing the preparation procedure for composite pellets using MgCl2 and silicone rubber, including such activation pretreatment, is shown in Figure 1.

[0026] The present invention further provides the use of the above-mentioned chemical heat storage material composition as a chemical heat pump combining an absorption exothermic reaction of NH3 and an endothermic desorption reaction of NH3. A chemical heat pump is an effective means as a system for recovering and reusing thermal energy. A chemical heat pump using a chemical heat storage material stores heat and outputs heat by utilizing a reversible reaction between an absorption exothermic reaction and an endothermic desorption reaction. For example, in the case of an MCl2 / NH3-based chemical heat pump, the heat generated when MCl2 in the chemical heat storage material composition absorbs NH3 to generate an NH3 complex can be released, and conversely, the NH3 complex can be heated to desorb NH3, thereby storing heat in the chemical heat storage material composition. By using the chemical heat storage material composition according to the present invention as a chemical heat pump, the volume change during operation at a low temperature range of around 100°C can be suppressed to a practical level, and a high heat output rate can be obtained from the beginning of operation. EXAMPLES

[0027] Specific examples of the present invention will be described below, but the present invention is not limited to these examples.

[0028] (Materials, etc.) For magnesium chloride (MgCl2), anhydrous MgCl2 with a purity of 98% manufactured by Kishida Chemical Co., Ltd. For ammonia (NH3), NH3 gas with a purity of 99.999% or higher manufactured by Showa Denko K.K. For nitrogen (N2), N2 gas with a purity of 99.999% or higher manufactured by Taiyo Nippon Sanso Corporation was used. The raw material for the elastomer was a one-liquid room temperature vulcanizing silicone rubber precursor (RTV rubber, KE-1825, Shin-Etsu Chemical Co., Ltd.). A mold for a heat press machine (inner diameter 7 mm) manufactured by AS ONE Corporation was used to mold the tablets.

[0029] (Reactivity test equipment) The reactivity of MgCl2 and NH3 was evaluated by measuring the mass change accompanying the NH3 absorption / desorption reaction of the sample using an NH3 supply type flow-type thermobalance device (TGD-9600) manufactured by Advance Riko Co., Ltd. The inside of the reactor of the thermobalance device was heated by infrared radiation from a heating furnace, and a mixed gas of NH3 / N2 was supplied from above the reactor in which the sample was present. The flow rates of NH3 and N2 were controlled by a readout unit (CR-400) connected to a mass flow controller (MFC, MODEL 3660) manufactured by Kofloc Corporation. The readout unit was connected to a PC via an interface converter (SI-35USB) manufactured by LINEEYE Co., Ltd., and the flow rate of the mixed gas was controlled on the PC. The total flow rate of each gas was set to a constant value of 50 mL / min (standard, 1 atm, 20°C), and the NH3 partial pressure was calculated from the flow rate ratio of the mixed gas.

[0030] The evaluation of chemical heat storage performance involves the heat storage density per mass and per volume q m [kJ kg -1 ] and q v [kJ L -1 The thermal output was evaluated using the thermal output density per mass and per volume q m,output [kJ kg -1 ] and q v,output [kJ L -1 The calculation formulas for each are shown below.

number

[0031] In addition, to calculate the rate of heat output and heat storage, the heat output rate per unit mass and per unit volume w m,output [kW kg -1 ] and w V,output [kW L -1 ], and the heat storage rate w m,storage [kW kg -1 ] and w V,storage [kW L -1 ] is defined.

number

[0032] Example 1 Composite pellets using MgCl2 and silicone rubber were prepared according to the procedure shown in Figure 1. The pestle and mortar used to mix MgCl2 and the RTV rubber precursor were pre-chilled in a refrigerator to prevent inhibition of precursor curing during mixing. In an argon-substituted glove box, MgCl2 and the RTV rubber precursor were mixed in any mass ratio using a pestle and mortar. The mixed sample was molded into pellets using the above-mentioned tablet molding die and table press under conditions of a pressure of 1 MPa and a pressing time of 1 minute.

[0033] The composite sample after molding was named "MgSiα" from the initials of the heat storage material MgCl2 and the binder silicone. α is the mixed mass ratio of the silicone precursor in the composite sample consisting of MgCl2 and the silicone precursor. For example, a composite sample mixed in a mass ratio of MgCl2:Si=6:4, such as MgCl2 (0.6 grams) and silicone precursor (0.4 grams), was named "MgSi0.4". In this embodiment, in addition to MgSi0.4, "MgSi0.25" and "MgSi0.3" were prepared in the same manner, with the silicone precursor mixed at different ratios. The molded MgSiα was polymerized with a silicone precursor in a drying oven at 130°C for 2 hours while maintaining the pellet shape, to obtain a composite pellet consisting of MgCl2 and silicone rubber.

[0034] (Pre-activation treatment) After polymerization, the composite pellets were subjected to an NH3 absorption reaction in a screw-cap bottle under an atmosphere of NH3 partial pressure of 100 kPa (gauge pressure), NH3 flow rate of 50 mL / min, and a first temperature of 25°C for 4 hours (first pretreatment stage). For samples whose pellet diameter expanded to 8 mm or more in the first pretreatment stage, a punch with an inner diameter of 7 mm was used to hollow them out. Next, the composite pellets that had undergone the first stage of pretreatment were subjected to an NH3 absorption reaction in the sample chamber of a thermobalance (TG) under an atmosphere of NH3 partial pressure of 100 kPa and NH3 flow rate of 50 mL / min at a first temperature of 25°C for 4 hours, and then heated to a second temperature of 100°C at a heating rate of 5°C / min while maintaining the atmosphere at NH3 partial pressure of 100 kPa, and held at 100°C for 15 minutes. Then, the operation of stopping heating and lowering the temperature to 25°C again was repeated until the mass did not increase after lowering the temperature. This second stage of pretreatment is called "pellet polymerization material in-TG activation pretreatment". The composite pellet sample that had undergone the pellet polymerization material in-TG activation pretreatment was hollowed out using a punch with an inner diameter of 7 mm, completing the activation pretreatment.

[0035] (Reactivity evaluation) The reactivity with NH3 was evaluated for the three composite pellet samples "MgSi0.25", "MgSi0.3" and "MgSi0.4" that had completed the activation pretreatment, using the following procedure. The target samples were placed in the heating furnace of the TG and heated to a reaction temperature of 165°C at a heating rate of 5°C / min under an atmosphere of N2 partial pressure of 100kPa, and NH3 was desorbed from the composite pellets to obtain MgCl2·2NH3. Thereafter, the absorption reaction conditions were NH3 partial pressure of 100kPa, absorption temperature (Ts) of 100°C, and 20 minutes, and the desorption reaction conditions were NH3 partial pressure of 5kPa, desorption temperature (Td) of 120°C, and 30 minutes, and the NH3 absorption / desorption reversible reaction test was repeatedly performed. The NH3 partial pressure was switched after the reaction system was stabilized for 5 minutes after the temperature was switched.

[0036] The absorption / desorption reversible reaction test was repeated 10 times, and the NH3 absorption behavior in the first cycle is shown in Figure 2, and the NH3 absorption behavior in the tenth cycle is shown in Figure 3. In all three composite pellet samples, as shown by the change over time in the number of moles of NH3 absorbed per mole of (MgCl2·2NH3), the progress of the NH3 absorption and desorption reactions sufficient for use as a chemical heat storage material at 120°C was confirmed. In addition, it was confirmed that the reaction rates of the absorption and desorption reactions in the 10th cycle were faster than those in the first cycle, and the absorption reaction was completed quickly in about 20 minutes, and the desorption reaction was completed quickly in about 30 minutes. For MgSi0.4, n=3.65 was recorded in the 10th cycle.

[0037] Figure 4 shows the appearance of the three types of composite pellet samples before and after the cyclic reaction test. The volume indicated by "V" in the figure is a value roughly calculated from the diameter and height of the composite pellet assuming a cylindrical shape. It was confirmed that the composite pellets did not collapse and maintained their shape even after 10 cycles of cyclic reaction tests in all three types of composite pellet samples. In MgSi0.25 and MgSi0.3, slight volume expansion and the occurrence of some cracks on the pellet surface were confirmed before and after the cyclic reaction, but in MgSi0.4, almost no volume expansion or cracks were observed before and after the cyclic reaction.

[0038] From the results of the repeated reaction test, the heat storage performance and heat output performance of MgSi0.4 were evaluated. Figure 5 shows the heat storage density and heat storage rate per unit volume of the chemical heat storage material. MgSi0.4 recorded a heat storage density per unit volume (left axis of the graph) of 754 kJ / L (984 kJ / kg) at the 10th cycle. This value is about 1.5 times higher than the heat storage density of the chemical heat storage material HASClay (registered trademark), which has a similar operating temperature range. In addition, the heat storage rate per unit volume (right axis of the graph) recorded a maximum value of 0.602 kW / L (0.816 kW / kg). Figure 6 shows the thermal output density and thermal output rate per unit volume of the chemical heat storage material. MgSi0.4 recorded a thermal output density per unit volume (left axis of the graph) of 748 kJ / L (976 kJ / kg) at the 10th cycle. In addition, the thermal output rate per unit volume (right axis of the graph) recorded a maximum value of 0.972 kW / L (1.27 kW / kg). These heat storage / thermal output performance data demonstrate that the composite pellets according to the present invention have the basic performance required for practical use as a chemical heat storage material.

[0039] Next, a demonstration test of operation as a chemical heat pump was carried out using the above composite pellets (MgSi0.4). The absorption process conditions were NH3 partial pressure 90 kPa and temperature 120°C, and the desorption process conditions were NH3 partial pressure 0 kPa (N2 supply environment) and temperature 90°C, and a repeated reaction test was carried out. The results are shown in Figure 7. It was confirmed that the composite pellets according to the present invention repeatedly reacted under the set conditions, and it was demonstrated that the chemical heat pump could be operated with an output heat of 120°C for an input heat of 90°C.

[0040] Example 2 As described above, the MgCl2 / NH3-based chemical heat storage material has an equilibrium temperature at which the reaction proceeds near 100°C, but the reactivity of NH3 absorption is low near 100°C, so the heat output rate is not sufficient for practical use as a chemical heat storage material in the low temperature range. The present inventors have investigated an activation method for increasing the heat output rate in such a low temperature range as follows. FIG. 8 shows the sample preparation procedure and reaction conditions for the MgCl2 / NH3-based chemical heat storage material, comparing the presence or absence of activation pretreatment.

[0041] To confirm the reactivity of anhydrous MgCl2 itself with NH3, repeated experiments were carried out under isothermal conditions. Approximately 10 mg of anhydrous MgCl2 was placed in a thermobalance apparatus (TG), and the reaction temperature (T) was raised to 100°C at 5°C / min. After the temperature stabilized, NH3 was supplied. The NH3 partial pressure (P NH3The partial pressure was then changed to 100 kPa and NH3 was absorbed for 30 minutes. The partial pressure was then changed to 5 kPa and NH3 was desorbed for 30 minutes. The absorption and desorption reactions every 30 minutes were counted as one cycle, and 15 cycles were repeated.

[0042] (Pre-activation treatment) In order to increase the reactivity of powdered magnesium chloride, NH3 was absorbed into anhydrous MgCl2 at room temperature to obtain MgCl2·6NH3, and then the temperature was raised to 165°C at 5°C / min in an NH3 atmosphere to desorb NH3 and obtain MgCl2·2NH3. This was the activation pretreatment process. To confirm the reactivity of the sample (MgCl2·2NH3) after activation pretreatment, the sample was placed in a TG and NH3 was supplied immediately after the start of the measurement. After the pretreatment, the atmosphere was switched to N2 gas and the temperature was lowered to a reaction temperature (T) of 100°C. 10 minutes after T=100°C, NH3 was supplied at an NH3 partial pressure of 100kPa to measure the absorption behavior.

[0043] (Reactivity evaluation) FIG. 9 shows the (a) change in the amount of NH3 absorbed and (b) the change in the absorption rate over time in the MgCl2 / NH3-based chemical heat storage material with or without activation pretreatment. In Figure 9(a), the horizontal axis shows time and the vertical axis shows the change in the number of moles absorbed, Δn, with the NH3 supply start time set to 0 min. The change in the number of moles absorbed within 10 min was only Δn = 0.8 for the material without activation pretreatment, but the sample with activation pretreatment recorded Δn = 4.0. The reaction rate was calculated from this and is shown in Figure 9(b). The material with activation pretreatment reached its maximum reaction rate within the initial 100 seconds of the reaction, a value that was 8.6 times higher than that of the material without activation pretreatment, confirming that the NH3 absorption reaction rate at 100 °C of the MgCl2·2NH3 sample after activation treatment was significantly higher than that of untreated MgCl2.

[0044] Figure 10 shows the time course of (a) the amount of NH3 absorbed in all cycles and (b) the change in the amount of NH3 absorbed during the absorption process in each cycle in a repeated reaction test at 100 °C for the preactivated MgCl2·2NH3 sample with an improved NH3 absorption reaction rate. From Fig. 10(a), it can be seen that the NH3 absorption and desorption reaction proceeds stably in the range of absorbed moles 2 to 6 in the activated pretreated MgCl2·2NH3 sample at each pressure change every 30 minutes. Also, from Fig. 10(b), it was confirmed that the absorption reaction was completed within 6 minutes, with Δn=4.0 at each cycle point. Thus, it was confirmed that the equilibrium reaction of MgCl2·2NH3+4NH3⇔MgCl2·6NH3 repeatedly proceeds in the vicinity of 100°C in the activated pretreated MgCl2·2NH3 sample, and the NH3 absorption reaction does not deteriorate even after an increase in the number of cycles, and is completed in a short time.

[0045] An operational demonstration test was conducted using the MgCl2 / NH3-based chemical heat storage material that had been pre-activated as a chemical heat pump. Using the pre-activated MgCl2·2NH3 sample, a repeated reaction test was conducted under absorption process conditions of NH3 partial pressure 90kPa and temperature 120℃, and desorption process conditions of NH3 partial pressure 5kPa and temperature 90℃. The results are shown in Figure 11. From Fig. 11(a), it can be seen that the NH3 absorption and desorption reactions proceed stably in the range of the amount of change in the number of moles absorbed, Δn = 0 to 4, for the activated pretreated MgCl2·2NH3 sample with each pressure and temperature change. Also, from Fig. 11(b), the amount of change in the number of moles absorbed, Δn, in the absorption process and the desorption process stabilized at 3.9 and 3.8, respectively, from the third cycle onwards. Thus, it was confirmed that the activated pretreated MgCl2·2NH3 sample according to the present invention repeatedly undergoes reactions under the set conditions, and it was demonstrated that the chemical heat pump can be driven with an output heat of 120°C for an input heat of 90°C. [Industrial Applicability]

[0046] Of industrial waste heat, 49%, or 364 PJ / y, is enormous. If the reaction activity and durability of this reaction system can be improved and it can be applied to the recovery and reuse of low-quality heat around 100°C, the effective use of low-quality waste heat can reduce the primary energy input, resulting in significant energy savings and making a major contribution to carbon neutrality in society.

Claims

1. Metal chlorides (MCi 2 ) and ammonia (NH 3 A chemical heat storage material consisting of Elastomer A chemical heat storage material composition having a predetermined shape comprising:

2. The chemical thermal storage material composition according to claim 1 , wherein the elastomer is a thermal addition crosslinking type silicone elastomer.

3. The metal chloride (MC 2 2. The chemical heat storage material composition according to claim 1, wherein the metal M is selected from the group consisting of magnesium (Mg), nickel (Ni), calcium (Ca), lead (Pb), cobalt (Co), copper (Cu), zinc (Zn) and manganese (Mn).

4. The metal chloride is MgCl 2 The chemical thermal storage medium composition according to claim 2 .

5. The chemical thermal storage material composition according to claim 1, wherein the mass ratio of the elastomer to the metal chloride is in the range of 0.1 to 0.

7.

6. Metal chlorides (MCi 2 ) and an elastomer precursor in a predetermined ratio to prepare a precursor composition; preparing a precursor composition having a predetermined shape by pressure molding the precursor composition; heating the shaped precursor composition to polymerize the elastomer precursor; and The composition having a predetermined shape after polymerization was added with ammonia (NH 3 A method for producing a chemical thermal storage material composition having a predetermined shape, comprising: subjecting the composition to an activation pretreatment in which the composition absorbs .

7. The method of claim 6, wherein the elastomer precursor is a thermal addition crosslinkable silicone.

8. The metal chloride (MC 2 7. The method according to claim 6, wherein the metal M is selected from the group consisting of magnesium (Mg), nickel (Ni), calcium (Ca), lead (Pb), cobalt (Co), copper (Cu), zinc (Zn) and manganese (Mn).

9. The method according to claim 6, wherein the mass ratio of the elastomer precursor to the metal chloride is in the range of 0.1 to 0.

7.

10. Magnesium chloride (MgCl 2 ) and ammonia (NH 3 A method for activating a chemical heat storage material comprising anhydrous MgCl 2 NH 3 at a first temperature to form MgCl 2 ・6NH 3 Then, the MgCl 2 ・6NH 3 NH 3 NH 3 By desorbing MgCl 2 ・2NH 3 The activation method according to claim 1,

11. 11. The activation method according to claim 10, wherein the first temperature is room temperature and the second temperature is 200°C or less.

12. N.H. 3 Absorption exothermic reaction of NH 3 Use of the chemical heat storage material composition according to claim 1 as a chemical heat pump in combination with an endothermic desorption reaction of

Citation Information

Patent Citations

  • Chemical heat storage device

    JP2015014234A

  • Chemical thermal storage medium, and composition for forming chemical thermal storage medium

    JP2016190990A